2022
DOI: 10.1049/rsn2.12256
|View full text |Cite
|
Sign up to set email alerts
|

A prior information‐based coverage path planner for underwater search and rescue using autonomous underwater vehicle (AUV) with side‐scan sonar

Abstract: The coverage path planning (CPP) technique attracts growing interest in studies on underwater search and rescue (SAR) conducted with an autonomous underwater vehicle (AUV) equipped with a side‐scan sonar (SSS). In SAR missions, prior information is crucial. Aiming at the underwater SAR mission with prior information, a new coverage path planner (SAR‐A*) is proposed. The ultimate goal is to generate a feasible path for completely covering the task area and preferentially visiting more valuable cells with fewer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Thomas et al proposed a novel metamodel to estimate the mission success possibility for a SAR task with the support of a supervised learning method [28]. Similar studies can be found in [29][30][31]. We find that the particle swarm optimization (PSO) method is commonly used to determine the optimization deployment strategy of maritime rescue facilities.…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…Thomas et al proposed a novel metamodel to estimate the mission success possibility for a SAR task with the support of a supervised learning method [28]. Similar studies can be found in [29][30][31]. We find that the particle swarm optimization (PSO) method is commonly used to determine the optimization deployment strategy of maritime rescue facilities.…”
Section: Introductionmentioning
confidence: 60%
“…We implemented the simulation with the help of accident data samples, main sea routes and an SAR rescue base station. Figure 3 demonstrates the distributions under different numbers of SAR rescue base stations (e.g., 5,10,15,20,25,30). Figure 3a illustrates the distributions of five ship base stations for an SAR task, whilst the x-axis and y-axis denote the latitude and longitude of each of the base stations.…”
Section: Sar Task Performance With Shipmentioning
confidence: 99%
“…There are available existing methods for this purpose, such as the lawnmower method [41,42], the spanning tree coverage method [43], and so on. However, considering the prior target information, we adopt our previously proposed SAR-A* [33], which is specifically designed for coverage path planning for AUVs equipped with SSS.…”
Section: Single-auv Coverage Path Planning Methodsmentioning
confidence: 99%
“…As for the single-robot coverage path planning method, the SAR-A* method, which we proposed previously [33], is employed to plan the AUV paths. For the discrete task area, the SAR-A* method generates a path through iteratively selecting optimal waypoints.…”
Section: Contributionmentioning
confidence: 99%
“…The primary goal of coverage path planning is to devise a path or trajectory for a vehicle or agent that maximizes the coverage of a specified area, minimizing redundancy and ensuring systematic exploration. Particularly, coverage path planning is a critical aspect of marine robotics, encompassing a wide range of applications like bathymetry mapping [122,123], underwater surveys [124,125], search and rescue missions [126,127], and mine-countermeasures [128,129]. By intelligently navigating through designated areas, AMVs can efficiently collect data, perform critical tasks, and contribute to a safer and more informed maritime environment.…”
Section: Coverage Planning Techniquesmentioning
confidence: 99%